PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN VALUE CLARIFICATION TECHNIQUE MODEL PERCONTOHAN DI KELAS IV B SDN 13 SURAU GADANG KOTA PADANG - Yona, Yona Adila; Yesi Anita; Reinita; Yanti Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the less than optimal learning outcomes of students, especially in the affective aspect. This study aims to describe the improvement of learning outcomes of Pancasila Education using the Value Clarification Technique Model Pilot in class IV B SDN 13 Surau Gadang, Padang City. This type of research is classroom action research (CAR), using qualitative and quantitative approaches. This research was conducted in two cycles, cycle I with two meetings and cycle II with one meeting. The subjects of this study were teachers, and students totaling 20 people. The results showed an increase in: 1) The average cycle I teaching module was 93.7% (Very Good), increasing in cycle II to 95.8% (Very Good). 2) The implementation of the teacher aspect in cycle I was 92.1% (Good), increasing in cycle II to 93.7% (Very Good). 3) The implementation of the student aspect in cycle I was 89% (Good), increasing in cycle II to 93.7% (Very Good). 4) The average learning outcomes of students in cycle I were 86.2 (Good), increasing in cycle II to 92.2 (Good).